Recovery Based Training - An Alternate Method of Athlete Preparation - Goldsmith, W. (coachesinfo.com)
There are no short cuts to the top. The attributes of success are now, as they always have been, determination, innovation, commitment, a positive attitude, the desire to achieve and old fashioned hard work. However, traditional ways of looking at training have revolved around - WORK BASED TRAINING: how much work an athlete can do and the intensity level of that work. Recovery has become an increasingly important aspect of athlete preparation. The demands of training schedules, competition programs and other related activities has necessitated athletes and coaches becoming more aware of the use of recovery techniques in planning and programming. The process of recovery is still very much that of "catch up" - ie the recovery techniques are generally utilised after the fact (after the athlete is fatigued) and are a peripheral aspect of training and competition. In some ways this is an ineffective use of recovery principles as the athlete could be exposed to significant stress before a recovery activity may be utilised. In addition, there is a significant amount of research that has identified the link between training and stress on the body's immune system leading to illness and disease. Ideally the athlete and coach would take a preventative approach to illness and be proactive with recovery and restoration practices to avoid or reduce the incidence of these problems. The challenge is to find ways to train athletes to achieve their maximum potential without pushing them "over the edge" into an overtrained or over reached situation with the subsequent health issues. This paper proposes an alternate model to the contemporary training methodologies which are WORK based by suggesting that programs can be RECOVERY BASED - ie based on the individual athlete's recovery abilities rather than on the volume and intensity workloads that an athlete can endure in a specific time. This model proposes that RECOVERY be considered as one of the central aspects of athlete development. The key to this approach is the philosophy - The intelligent coach bases their training and competition progam around their athlete's ability to recover.